2012
DOI: 10.1007/s00213-012-2833-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic evidence to support clinical decision making for peripartum methadone treatment

Abstract: Rationale Limited pharmacological data are available to guide methadone treatment during pregnancy and postpartum. Objectives Study goals were to: 1) Characterize changes in methadone dose across childbearing, 2) Determine enantiomer-specific methadone withdrawal kinetics from steady-state during late pregnancy, 3) Assess enantiomer-specific changes in methadone level/dose (L/D) ratios across childbearing, and 4) Explore relationships between CYP2B6, CYP2C19 and CYP3A4 single nucleotide polymorphisms and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
1
22
0
2
Order By: Relevance
“…For example, none of the studies that investigated antibiotics [47,52,53] or anesthetic and analgesic drugs [102] provided data on clinical outcomes. On the other hand, studies of addiction management drugs and antidepressant drugs reported clinical data, showing a positive correlation between decreased drug exposure and diminished clinical effects in pregnancy [70,202]. A study investigating cardiovascular drugs that reported clinical outcomes did not demonstrate significant positive clinical correlations [127].…”
Section: Discussionmentioning
confidence: 99%
“…For example, none of the studies that investigated antibiotics [47,52,53] or anesthetic and analgesic drugs [102] provided data on clinical outcomes. On the other hand, studies of addiction management drugs and antidepressant drugs reported clinical data, showing a positive correlation between decreased drug exposure and diminished clinical effects in pregnancy [70,202]. A study investigating cardiovascular drugs that reported clinical outcomes did not demonstrate significant positive clinical correlations [127].…”
Section: Discussionmentioning
confidence: 99%
“…27 Similarly, methadone metabolism varied with the specific genotype of CYP2B6. 28 Enzyme activity varies with ethnicity, gender, age, and certain disease states that are unrelated to pregnancy. Commonly, enzymes have numerous substrates, and different drugs may undergo metabolism by several enzymes.…”
Section: Drug Metabolismmentioning
confidence: 99%
“…Swift et al (1989) in a single case study calculated a methadone half-life of 8.1 hours, which they felt documented the need for an altered dosing regimen in pregnancy. Finally, a recent study of methadone pharmacokinetics across childbearing documented shorter half-life (as low as 11 hours) and larger clearances during pregnancy, prompting the authors to conclude that "serious consideration should be given to offering women split methadone dosing" (Bogen et al, 2013). Despite the forgoing evidence, single dose regimens remain the common practice, including being used as the comparator condition in the National Institute of Drug Abuse study comparing the use of methadone and buprenorphine in pregnancy (Jones et al, 2010).…”
mentioning
confidence: 97%